PROFIL KEMAMPUAN BERPIKIR KREATIF SISWA KELAS X SMK NEGERI 7 ENDE - Mako, Simplisia Yosefina; Harso, Aloisius; Kaleka, Melkyanus Bili Umbu (EduFisika: Jurnal Pendidikan Fisika, 2020)
This study aims to describe the profile of creative thinking skills in class X SMK Negeri 7 Ende. This type of research is descriptive research. The research subjects were students of class X AP, totaling 23 people. The data obtained are in the form of test scores for creative thinking skills. Data were analyzed descriptively. The results showed that the ability to think creatively for all indicators was obtained an average of 90.2% in the very creative category. The creative thinking skills studied include flexible, fluent, original thinking, detailing and evaluating.